Teacher Dependency and Parental Absence as a Lopsided Support System in Yi Minority English Education - Yang, Demei; Chen, An (Journal of Qualitative Research in Education, 2025)
English education in China' s ethnic minority regions faces unique hurdles under the "Sanyu Jiantong" trilingual policy, yet the micro-level dynamics of how social support systems function in these contexts remain underexplored. Integrating Bronfenbrenner' s Bioecological Model with Bourdieu' s Theory of Capital, this qualitative single-case study investigates the support network of Grade 9 students in Mabian Yi Autonomous County. Leveraging the researcher' s "emic" perspective, data were collected through semi-structured interviews with students, parents, and a teacher, alongside extensive classroom and field observations. Our analysis reveals a stark "support imbalance" rooted in socio-economic disparities. Specifically, a dual deficit in familial cultural and economic capital results in a "structural absence" of informational and instrumental support at home. This leaves students in a state of "monopolar dependency", relying almost exclusively on their English teacher for guidance. However, this overburdened teacher, trapped in a structural double bind, adopts pragmatic strategies of "academic triage", leading to a "tacit agreement" of disengagement with struggling students. We conclude that the underperformance in English education in these regions is a complex socio-ecological dysfunction, not merely a pedagogical issue. The study argues that the current model, which asks the teacher to stand as a "lone pillar", is unsustainable. Future interventions must move beyond simple fixes to rebuild the entire support ecosystem, potentially repositioning schools as digital facilitators to bridge the capital gap and empower the marginalized learner.